Effects of a Health Belief Enhancing Program on Perception and Coronavirus 2019 Vaccination Receiving Among Elderly Population in Savannakhet Province, LAO PDR - Saiyasith, Paliya; Mangkarakeree, Nutcharat; Tamdee, Decha (Journal of The Royal Thai Army Nurses, 2024)
This quasi-experimental research with a two-group pretest-posttest design. The research objectives were to study the Effects of a Health Belief Enhancing Program on Perception and coronavirus-2019 Vaccination Receiving Among the Elderly Population in Savannakhet Province, LAO PDR.The study included 48 elderly participants from Savannakhet province, divided into two groups: one group that received the program (experimental group, 24 individuals) and another that did not(comparison group, also 24 individuals). The study lasted for 6 weeks. To collect data, using questionnaires to measure Perception and coronavirus 2019 Vaccination Receiving The reliability was .76 and.95 respectively. The data were analyzed by descriptive statistics, the Paired t-test, and the independent t-test. The study’s findings revealed that, after participating in the program, the experimental group’s average scores for COVID-19 awareness significantly increased compared to their scores before the program (p = .002). Furthermore, their awareness scores were significantly higher than those of the comparison group (P< .05). The results revealed that the healthcare personnel can apply this Health Belief Enhancement Program for the elderly to improve COVID-19 prevention this time for encouraging elderly people in other areas to come and receive the vaccination against further diseases.